2021
DOI: 10.3390/diagnostics11071298
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Neutrophil-to-Lymphocyte Ratio during Neoadjuvant Chemotherapy as a Predictive and Prognostic Marker in Advanced Ovarian Cancer

Abstract: Since chronic inflammation is associated with ovarian cancer growth and progression, some clinical studies have assessed the association between the pre-treatment neutrophil-to-lymphocyte ratio (NLR) and the prognosis of ovarian cancer. The purpose of this study was to assess the dynamic behavior of the NLR during the course of neoadjuvant chemotherapy (NACT) in patients with high grade serous (HGS) advanced epithelial ovarian cancer and assess its correlation with clinical response, progression free survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
(53 reference statements)
1
22
0
Order By: Relevance
“…All selected articles passed the STROBE checklist criteria (Supplementary Table S2). These include the articles of Sanna et al [35], Micheli et al [36], de Lima et al [37], Rodrigues et al [38], Kampan et al [25], Wertel et al [39], Zhang et al [40], Crispim et al [41], Shi et al [42], Li et al [43], Dalal et al [44], Han et al [45], Kumar et al [46], Martins-Filho et al [47], Cantón-Romeo et al [48], Sanguinette et al [49], Hao et al [50], Mikuła-Pietrasik et al [51], Chudecka-Głaz et al [ S1 and S2).…”
Section: Strobe Checklistmentioning
confidence: 99%
“…All selected articles passed the STROBE checklist criteria (Supplementary Table S2). These include the articles of Sanna et al [35], Micheli et al [36], de Lima et al [37], Rodrigues et al [38], Kampan et al [25], Wertel et al [39], Zhang et al [40], Crispim et al [41], Shi et al [42], Li et al [43], Dalal et al [44], Han et al [45], Kumar et al [46], Martins-Filho et al [47], Cantón-Romeo et al [48], Sanguinette et al [49], Hao et al [50], Mikuła-Pietrasik et al [51], Chudecka-Głaz et al [ S1 and S2).…”
Section: Strobe Checklistmentioning
confidence: 99%
“…Hence, leukocytosis with high NLR alone related to the progression of the neoplastic disease may not be a determining prognostic factor, as we have recently clearly demonstrated in ovarian cancer. Indeed, in advanced ovarian cancer patients, we found that pretreatment NLR value does not represent a prognostic, while the increase in the number of lymphocytes, and consequently the reduction of NLR, during the chemotherapy regimen constitutes one of the most valid predictors of response to treatment and patient prognosis [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical studies have reported the correlation between pre-treatment NLR and the prognosis of cervical cancer [ 49 , 55 ]. Meanwhile, more recently, we have demonstrated in a population of patients with ovarian cancer that the pretreatment NLR value does not constitute a prognostic and predictive factor, but only the evidence of the extent of the systemic inflammation in progress; conversely, the increase in the number of lymphocytes during chemotherapy treatment, and therefore the reduction of NLR, constitutes one of the most valid predictors of response to treatment [ 56 ].…”
Section: Leukocytosis and Prognosis In Cervical Cancermentioning
confidence: 99%
“…In recent years, the relationship between the neutrophil-to-lymphocyte ratio (NLR) and malignant tumors has gradually attracted increasing attention from scholars, and studies have confirmed that NLR can predict patient prognosis in breast, liver, lung, and bladder cancers, these studies showed that a higher level of NLR was associated with a poor prognosis ( 5 - 8 ). Studies have also shown that NLR is associated with the efficacy of neoadjuvant chemotherapy in patients with ovarian cancer, a higher level of NLR is associated with a poor efficacy of neoadjuvant chemotherapy ( 9 , 10 ), but whether this change in efficacy translates into a long-term mortality benefit is unclear. Therefore, we designed this study to explore the correlation between the NLR and clinicopathological parameters in patients with epithelial ovarian cancer and its effect on prognosis, so as to promote the application of NLR in patients with ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%